An acute and fatal case of human leptospirosis in Sabah, Malaysia. - Bahaman, Abdul Rani; Bejo, Siti Khairani; Md Yasin, Rohani; Hiu, Jessie (2002)

(untitled)
An acute and fatal case of leptospirosis in a young man is described. Tissue samples from various internal organs examined by polymerase chain reaction (PCR) assay were positive for leptospiral DNA. The presence of specific leptospiral DNA as evident through PCR in all the organ samples except the lungs, were indicative of an acute and septicaemic disease. It was shown that PCR is a simple and rapid assay that could be used to diagnose cases of leptospiral infection.